Tracking of STAT3 signaling for anticancer drug-discovery based on localized surface plasmon resonance. Issue 8 (21st March 2016) - Song, Sojin; Nguyen, Anh H.; Lee, Jong Uk; Cha, Misun; Sim, Sang Jun
Abstract : The label-free sensor, based on the LSPR shift response by tracking of the STAT3 signaling pathways, is an ultrasensitive for drug screening of anticancer therapy. Abstract : Signal transducer and activator of transcription 3 (STAT3) protein signaling is crucial for the survival, invasion, and growth of human cancer cells; thus, STAT3 protein is an ideal target for a new drug screening system. Herein, we developed a label-free sensor for anticancer drug-discovery based on the localized surface plasmon resonance (LSPR) shift response by tracking of STAT3 signaling including phosphorylation and dimerization. This enables ultrasensitive monitoring of the molecular interactions that occur on the surface of single gold nanoparticles. The red shift of the LSPR λ max was observed as 3.46 nm and 9.00 nm, respectively, indicating phosphorylation and dimerization of the STAT3 signaling pathway. In screening of anticancer candidates, the system worked well in the presence of STA-21 which inhibits STAT3 dimerization. The LSPR λ max shift in the inhibition condition is three times lower than that in the absence of an inhibitor. Interestingly, the system reveals high specificity, reproducibility and compatibility with real samples (MCF-7 cell line). Therefore, these results demonstrated that this system has strong potential to be an accurate and effective sensor for tracking of signaling pathways and drug screening of anticancer candidates for anticancer therapy.